2007
DOI: 10.1007/s00442-007-0852-6
|View full text |Cite
|
Sign up to set email alerts
|

Tree proximity, soil pathways and common mycorrhizal networks: their influence on the utilization of redistributed water by understory seedlings

Abstract: Hydraulic redistribution (HR) is a process by which water moves through plant roots from moist to dry soils. An experiment was conducted to quantify the influence of common mycorrhizal networks (CMNs) and proximity to mature HR-source trees on the water relations of surrounding seedlings. Douglas-fir (Pseudotsuga menziesii var glauca (Mirb.) Franco) seedlings were planted at four distances (0.5, 1, 2.5, and 5 m) from six mature Douglas-fir trees, either directly into soil (soil plus CMN pathway) or inside 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…That this MN effect was not confounded by the presence of the mesh bag was confirmed by field observations of root distribution and Oecologia (2008) 158:193-203 195 root biomass data (see ''Results'') showing that seedlings grown in the no-mesh treatment had access to the same volume of soil as seedlings in mesh bags. We also found that seedlings in the no-mesh treatment took up the same amount of hydraulically redistributed water as seedlings in mesh bags (Schoonmaker et al 2007), confirming the absence of a ''bag effect''.…”
Section: Site Description and Experimental Designsupporting
confidence: 50%
See 2 more Smart Citations
“…That this MN effect was not confounded by the presence of the mesh bag was confirmed by field observations of root distribution and Oecologia (2008) 158:193-203 195 root biomass data (see ''Results'') showing that seedlings grown in the no-mesh treatment had access to the same volume of soil as seedlings in mesh bags. We also found that seedlings in the no-mesh treatment took up the same amount of hydraulically redistributed water as seedlings in mesh bags (Schoonmaker et al 2007), confirming the absence of a ''bag effect''.…”
Section: Site Description and Experimental Designsupporting
confidence: 50%
“…Facilitation was likely the result of an increase in EM status (colonization, richness, and diversity) (Cline et al 2005;Teste et al, in review), MN potential (Teste 2008), greater available soil water via hydraulic redistribution (Schoonmaker et al 2007), and perhaps nutrient sharing via MNs (Selosse et al 2006). Competition resulted from the presence of mature trees and surrounding AM plants, but this varied spatially.…”
Section: Facilitation and Competition Dynamicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Colonization of seedling roots by ectomycorrhizal (EcM) fungi can provide greater access to nutrients and water (Schoonmaker et al, 2007) and promote carbon cycling (Talbot et al, 2008). Bacteria associated with EcM are known to mobilize key nutrients from minerals and organic substrates (Burke et al, 2008;Frey-Klett et al, 2007) , while many key processes, such as nitrogen fixation, can be carried out by bacteria living freely in the soil (Izquierdo and Nüsslein, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In similar forests nearby, we have proven this experimentally, showing that seedling establishment success increased substantially where they had full access to the network of older Douglas-fir trees (Teste and Simard 2008;Teste et al 2009b). Access to the network not only improved seedling survival and physiology, but this was associated with colonization of the seedlings by a more complex fungal community as well as carbon, nitrogen and water transfer from the older trees (Schoonmaker et al 2007;Teste et al 2009a, b). The finding that the network had scale-free properties suggests that removal of hub trees can have negative effects on the regeneration system.…”
Section: Mycorrhizal Network In Complexmentioning
confidence: 99%